Comparison between Gibson–Cooke and Macroduct Methods in the Cystic Fibrosis Neonatal Screening Program and in Subjects Who Are Cystic Fibrosis Screen-Positive with an Inconclusive Diagnosis - Dolce, Daniela; Fevola, Cristina; Camera, Erica; Orioli, Tommaso; Lucenteforte, Ersilia; Malanima, Marco Andrea; Taccetti, Giovanni; Terlizzi, Vito (International journal of neonatal screening, 2023)
The sweat test (ST) is the current diagnostic gold standard for cystic fibrosis (CF). Many CF centres have switched from the Gibson–Cooke method to the Macroduct system-based method. We used these methods simultaneously to compare CF screening outcomes. STs using both methods were performed simultaneously between March and December 2022 at CF Centre in Florence. We included newborns who underwent newborn bloodspot screening (NBS), newborns undergoing transfusion immediately after birth, and children with CF screen-positive, inconclusive diagnosis (CFSPID). We assessed 72 subjects (median age 4.4 months; range 0–76.7): 30 (41.7%) NBS-positive, 18 (25.0%) newborns who underwent transfusion, and 24 (33.3%) children with CFSPID. No significant differences were found between valid sample numbers, by patient ages and groups (p = 0.10) and between chloride concentrations (p = 0.13), except for sweat chloride (SC) measured by the Gibson–Cooke and Macroduct methods in CFSPID group (29.0, IQR: 20.0–48.0 and 22.5, IQR: 15.5–30.8, respectively; p = 0.01). The Macroduct and Gibson–Cooke methods showed substantial agreement with the SC values, except for CFSPID, whose result may depend on the method of sweat collection. In case of invalid values with Macroduct, the test should be repeated with Gibson–Cooke method.